Development of Personal and Professional Competence of Senior Pupils by Interactive Learning Methods - Kovalevskaya, Ekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article describes the results of a study on the development of personal and professional competence of senior pupils by interactive learning methods. The author gives a Scale diagnostic personal and professional competence of senior pupils, as well as describes the results of a formative experiment, in which the program was implemented psycho-pedagogical support of career self-determination of senior pupils. Furthermore, the study considers the effectiveness of the four groups of interactive methods in the development of personal and professional competencies: methods of psychological training, cognitive and gaming methods, and techniques of art-therapy.